Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1177/0885066617696848
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Usability of Computerized Critical Care Information Systems in Germany

Abstract: Our results suggest that manufacturers should shift some of their effort away from the development of new features and focus more on improving the ease-of-use and quality of existing features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
(91 reference statements)
1
3
0
1
Order By: Relevance
“…To our best knowledge, this is the first study to investigate the usability of a homegrown venous thromboembolism prophylaxis recommendation system in the ICU setting of Nemazee hospital. These results concur with the other studies which have shown that clinical decision support system usability quality was good [10][11][12]. In contrast to some reports in the literature, there was usability quality of clinical information systems was low [7,13].…”
Section: Discussionsupporting
confidence: 89%
“…To our best knowledge, this is the first study to investigate the usability of a homegrown venous thromboembolism prophylaxis recommendation system in the ICU setting of Nemazee hospital. These results concur with the other studies which have shown that clinical decision support system usability quality was good [10][11][12]. In contrast to some reports in the literature, there was usability quality of clinical information systems was low [7,13].…”
Section: Discussionsupporting
confidence: 89%
“…The advantages of PDMS in ICUs have been emphasized in the literature [16]. The usability of PDMS in terms of support for medical decision making during rounds or ICU admissions, however, still is far from optimal [12,[17][18][19]. A PDMS should allow a rapid, systematic and complete visual check of all relevant patient data including labs, imaging, ECGs, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Secara peringkat kegunaan, pada umumnya suatu sistem lebih bergantung pada aspek kemudahan penggunaan daripada aspek fungsionalitas. (Dincklage, 2017) Hasil pengujian usability terhadap aplikasi sistem informasi wisata Pulau Ambon berbasis Android mampu memberikan informasi tempat wisata, kegiatan wisata dan daftar kuliner yang bisa digunakan wisatawan untuk lebih memudahkan mereka dalam merencanakan tujuan wisata yang diinginkan. Hasil analisis terhadap responden juga menunjukkan bahwa aplikasi sudah cukup memenuhi kelima aspek usabillity, diantaranya yaitu learnability, eficiency, memorability, errors, dan satisfaction.…”
Section: Kesimpulan Dan Saranunclassified